Nucleic Acid Biosensors for Environmental Pollution Monitoring - Mascini, Marco; Palchetti, Ilaria; Ozsos, Mehmet S.; Erdem, A.; Marrazza, Giovanna (Cambridge ; LaVergne : Royal Society of Chemistry, 2011)
Annotation Nucleic acids are the fundamental building blocks of life and are found in all living things. In recent years, their functions have been shown to extend beyond the Watson-Crick base pair recognition of complementary strands. Molecules (known as aptamers) consisting of 40-50 nucleotides have been isolated that are able to bind a broad range of molecules with high affinity and specificity. The molecules recognized by aptamers range from small organic molecules to proteins, cells and even intact viral particles. Catalytic DNA molecules called NAzymes (RNAzyme or DNAzyme) have also been shown to exist and, when combined with aptamers, are known as aptazymes. These biomolecules can be used to develop smart and innovative biosensors for environmental analysis. Monitoring of contaminants in the air, water and soil is a key component in understanding and managing risks to human health and ecosystems. This, in conjunction with the time and cost involved in traditional chemical analysis, means there is a growing need for simple, rapid, cost-effective and portable screening methods. Biosensors are compact devices which complement current field screening and monitoring methods. This book demonstrates the incredible opportunities that nucleic acids can offer to environmental analytical chemistry. The chapters: show how nucleic acids have a pivotal role in the development of smart biosensors for environmental monitoring; describe the development of biosensors based on aptamers and NAzymes for the detection of organic and inorganic pollutants; deal with the use of nucleic acid based biosensors for environmental toxicity screening, and detail the use of nanomaterials, as well as miniaturization and lab-on-a-chip technologies, for nucleic acid based biosensing systems.
College Audience